REAPING THE WHIRLWIND OF CHANGE: EASTERN CAPE WHITE COMMERCIAL FARMERS’ DISCOURSES OF DEMOCRACY - Bohmke, Werner; Neves, David (PINS-Psychology in Society, 2026)
This paper deals with the accounts of Eastern Cape white commercial farmers on the subject of Democracy. Drawing on the methodology of Discourse Analysis, the paper seeks to provide an analysis of the rhetorical strategies and ideological positions within the participants’ accounts. Such accounts of the social, historical and political circumstances in which farmers find themselves are thought to provide insight into the manner in which the process of democratic change has been received by members of the agricultural sector. Data collection was conducted via brief, audio taped, semi structured interviews. Participants were white men and women, Jiving in a commercial farming region of the Eastern Cape Province. Responses to the interviews were analysed according to the discursive approaches advanced by both Ian Parker and Jonathan Potter & Margaret Wetherell. Analyses reveal that participants tend towards criticism of the notion of democracy from a particularly liberal ideological standpoint and make use of notions and techniques of "Othering" to construct a defensive subject positioning. These findings illustrate what is in many ways still an ongoing political and ideological struggle in the rural regions of the country.